Phonons and rotons of trapped atoms in gravitational field - Baranov, D.B.; Yarunin, V.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The excitations of trapped atoms with a Bose-Einstein condensate in a trap are determined by the conservation of common phonon and roton numbers of atomic motion, and these properties depend on the presence of gravitational field.